Health Crises and Media Discourses in Sub-Saharan Africa - Dralega, Carol Azungi; Napakol, Angella (Springer Nature, 2022)
This is an open access book which brings together leading scholars and critical discourses on political, economic, legal, technological, socio-cultural and systemic changes and continuities intersecting media and health crises in Sub-Saharan Africa. The volume extensively discusses COVID-19 but it also covers other epidemics, such as malaria, HIV/AIDS as well as "silent" health crises such as mental health---simmering across the subcontinent. The chapters fill knowledge gaps, highlight innovations, unpack the complexities surrounding the media ecosystem in times of health crises. They explore, among other issues, the politics of public health communication; infodemics; existential threats to media viability; draconian legislations; threats to journalists/journalism; COVID-related entrepreneurship, marginalization, and more. This is a timely resource for academics, advocacy groups, media practitioners and policy makers working on crises and media reporting, not just in Africa but anywhere in the global South.